Higher education in liquid modernity - Oxenham, Marvin (New York : Routledge, 2013)
'Based in sociologist Zygmunt Bauman's theory of liquid modernity, this volume describes and critiques key aspects and practices of liquid education--education as market-driven consumption, short life span of useful knowledge, overabundance of information--through a systematic comparison with ancient Greek'paideia' and medieval university education, producing a sweeping analysis of the history and philosophy of education for the purpose of understanding current higher education, positing a more holisitic alternative model in which students are embedded in a learning commutity that is itself embedded in a larger society. If liquid modernity has left a vacuum where, according to Bauman, the pilot's cabin is empty, this volume argues that no structure is better positioned to fill this vacuum than the university and outlines a renewed vision of social transformation through higher education'--
Includes bibliographical references and index.
Keywords: Education, Higher -- Philosophy; Postmodernism and higher education; Holistic education